Crowd Funding, Social Entrepreneurship and Sustainable Development - Hery Wibowo (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The issues of sustainable Development is a mainstream issues of the nation. The participation of the citizen, is absolutely important for the sustainable of nation Development. However, until today, not many framework that describe in detail the pattern of collaboration between the goverment and its peopleThis paper is going to focus on two main community based activity from the third sector that is becoming emerging for the need of sustainable Development. The two activities are crowd funding and the activity launched by the citizen that bring innovation solutions to social problem: social entrepreneurship.Crowd funding is actually a unique activity, lauched by the citizen to help other parts of the community using all the potential resources. Crowdfunding takes advantages of crowd-based decision-making and innovation and applies it to the funding of projects or businesses. One of the practice that becoming populer and getting attention worldwide as a partner of nation development activity is social entrepreneurship. A social entrepreneurship practice is a community based action that have potential to help the nation development processes. Many studies stated that this practice have brought advantages the community, but on the other hand, the government haven’t fully promote the collaboration with them for the purpose of sustainable development. This article will try to analyze the potential of crowd funding and the activities of social entrepreneurship to become a partner of development undertaken by the goverment. Furthermore, on a broader scale, this paper also explores the role of the third sector to the development process. Finally, as a conclusion, a theoritical framework of the collaboration between crowd funding, social entrepreneurship and sustainable development is built, to complete this article